Evolution of the Collquepucre, Llongote, Pariacaca and Ticcla glaciers in the Cañete river basin - Alva Huayaney, Miguel (2018)
In the Cañete River Basin, a glacial retreat has been observed for more than 37 years. Based on aerial photographs for the years 1962 and 1970, and using Landsat images from the 1990 - 2015 period, the glacier surface of the Collquepucre, Llongote, Pariacaca and Ticcla snowfalls has decreased by 2 to 7 km2, for every 5 years; a situation that is related to the dynamics of tropical glaciers where various sources indicate that they are the most fragile ecosystems in the face of climate change.